The reaction quotient $Q_c$ is calculated as:
$Q_c = \frac{[B][C]}{[A]^2} = \frac{(2 \times 10^{-3})(2 \times 10^{-3})}{(2 \times 10^{-3})^2} = 1$.
Since $Q_c > K_c$, the reaction will shift in the backward direction to establish equilibrium.
The reaction quotient \( Q_c \) is given by:
$$ Q_c = \frac{[B][C]}{[A]^2} $$
Substitute the given concentrations:
$$ Q_c = \frac{(2 \times 10^{-3})(2 \times 10^{-3})}{(2 \times 10^{-3})^2} = \frac{4 \times 10^{-6}}{4 \times 10^{-6}} = 1 $$
The equilibrium constant \( K_c \) is given as \( 4 \times 10^{-3} \).
Since \( Q_c = 1 \) and \( K_c = 4 \times 10^{-3} \), we see that:
$$ Q_c > K_c $$
When \( Q_c > K_c \), the reaction proceeds in the backward direction to achieve equilibrium.
Therefore, the reaction will shift to the left, and there is a tendency for the reaction to go in the backward direction.
The correct answer is:
Option (3): The reaction has a tendency to go in the backward direction.
Identify the major product C formed in the following reaction sequence:
List-I | List-II | ||
(A) | 1 mol of H2O to O2 | (I) | 3F |
(B) | 1 mol of MnO-4 to Mn2+ | (II) | 2F |
(C) | 1.5 mol of Ca from molten CaCl2 | (III) | 1F |
(D) | 1 mol of FeO to Fe2O3 | (IV) | 5F |